Epidemiological Characteristics of Peripheral T-Cell Lymphoma: A Population-Based Study - Liu, Shuo; Liu, Weiping; Li, Huichao; Yang, Lei; Song, Yuqin; Zhang, Xi; Cheng, Yangyang; Li, Qingyu; Li, Haoxin; Wang, Ning; Zhu, Jun; Ji, Jiafu (Frontiers in Oncology, 2022)
Objects: To explore the epidemiological characteristics of peripheral T cell lymphoma in Beijing. Methods: All of the data were extracted from the Beijing Cancer Registry database from 1st Jan. 2007 to 31st Dec. 2018. Segi’s World Standard Population was used to estimate age-standardized rate (ASR). Changes in trends were examined using join-point regression analysis. The observed survival was estimated by the Kaplan-Meier method. Relative survival was calculated using Ederer II and standardized using the Brenner method and ICSS group 1 age structure. Stratified by gender, region, and histological type, incidence, mortality, and age of onset trends were observed in Beijing. Results: In Beijing, there were 801 new cases and 463 deaths of T cell lymphoma from 2007 to 2018. Peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS), was the most prevalent subtype (37.45%), followed by angioimmunoblastic T cell lymphoma (AITL, 20.35%), NK/T cell lymphoma (NK/TCL, 17.60%) and anaplastic large cell lymphoma (ALCL, 10.24%). The crude incidence and mortality rates were 0.52 and 0.30 per 100,000 person-year, while the age-standardized incidence and mortality rates (ASIR and ASMR) were 0.35 and 0.18 per 100,000 person-year, respectively. Both ASIR and ASMR were more prevalent in males (0.48 and 0.24 per 100,000) and urban area (0.38 and 0.19 per 100,000) than in female (0.22 and 0.11 per 100,000) and rural area (0.30 and 0.15 per 100,000). The average annual percentage change (AAPC) of ASIR and ASMR was 5.72% (95% CI 1.79%-9.81%) and 4.35% (95% CI -0.09%-8.99%), respectively. The age-specific incidence rate increased with age and peaked at the age groups of 10-14 and 80-84. The mean and median age of onset increased between 2007 and 2018. In addition, it decreased after the age of onset was age-standardization (β=-0.41, P=0.26). The 5-year age-standardized relative survival was 39.02% for all patients, 58.14% for NK/TCL, 57.60% for ALCL, 31.38% for AITL, and 29.18% for PTCL-NOS. Conclusions: T cell lymphoma incidence was rising, but survival was dismal in Beijing, indicating the need for improved early diagnosis and standardized treatment.